Prolactin is a Key Factor for Nonalcoholic Fatty Liver Disease in Obese Children - Zhang, Jianwei; Guan, Jieqiong; Tang, Xiaoli; Xu, Jinliang (Hormone and Metabolic Research, 2023)
This study investigates whether serum prolactin (PRL) is a key factor for nonalcoholic fatty liver disease (NAFLD) in children. A total of 691 obese childred participated in this study and were divided into a NAFLD group (n=366) and simple obesity (SOB) group (n=325) according to the hepatic ultrasound results. The two groups were matched for gender, age, pubertal development, and body mass index (BMI). All patients underwent an OGTT test, and fasting blood samples were collected to measure prolactin. Stepwise logistic regression was performed to identify significant predictors of NAFLD. Serum prolactin levels were significantly lower in NAFLD subjects than in the SOB subjects [82.4 (56.36, 118.70) vs. 99.78 (63.89, 153.82), p<0.001] (mIU/l). NAFLD was strongly associated with insulin resistance (HOMA-IR) and prolactin, with lower levels of prolactin increasing the risk of NAFLD (adjusted ORs=1.741; 95% CI: 1.059–2.860) across the prolactin concentration tertiles after adjustment for confounders. Low serum prolactin levels are associated with the presence of NAFLD; thus, increased circulating prolactin might be a compensatory response for obesity in children.
Keywords: children; nonalcoholic fatty liver disease; prolactin; obesity; metabolic syndrome